Optical and Electro-Optical Properties of YbFe2O4 Thin Films (Journal of Nepal Physical Society, 2021)
We present the optical and electro-optical properties of YbFe2O4 thin films, deposited on (0001) sapphire substrates. The optical spectra of YbFe2O4 show several electronic peaks arising from Fe2+ d to d on-site and O 2p to Fe 3d, Yb 6s, and Yb 5d charge-transfer transitions. The temperature dependence of the d to d electronic transition displays an anomaly around 150 K, which could be associated with a structural instability. Moreover, the YbFe2O4 thin film show strong electric-field-induced changes in optical properties in the energy range of 1-3 eV for applied electric fields less than 1 kV/cm. These electro-optical effects, which vary almost linearly with applied electric fields, are up to 14 % in magnitude at low temperatures and the effects completely disappear above 120 K. The observed electro-optical effects could be associated with the effects of external electric fields on the orbital-charge ordering of Fe ions.